Exploring sustainability literacy: developing and assessing a bottom-up measure of what students know about sustainability - Kuehl, Colin; Sparks, Aaron C.; Hodges, Heather; Smith, Eric R. A. N. (Frontiers in Sustainability, 2023)
With many organizations, particularly higher education institutions, placing a priority on sustainability education it is important to have a measure of sustainability knowledge to assess growth over time. There have been several attempts using differing approaches to develop a valid assessment tool. However, given wide-ranging conceptual definitions of sustainability and diverse instructional techniques, we are skeptical that sustainability is a concept that can adequately be measured. The existing measures were developed using a top-down approach to question inclusion the questionnaire. As an alternative, in this paper we develop a new measure, using a bottom-up approach. In Study 1 with a sample from the University of California, Santa Barbara, we test the 44 item instrument with a large student sample. In Study 2, with a sample from Northern Illinois University, we test a shortened 10 item instrument in a different student population. Across both studies, we find little evidence for a coherent structure to sustainability knowledge. Yet, the 10 item measure correlates highly with the longer version and may be suitable to other research applications.